Bilateral Temporal Bone Fracture: aural rehabilitation of a rare case - Sara Azevedo; João Vale Lino; Miguel Bebiano Coutinho; Luis Meireles (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Temporal bone fracture and related sequelae may not represent the patient’s most immediately threatening problems. However, early involvement of the otolaryngologist in evaluation and management can improve long-term functional outcome.